A randomized, open-label, Phase III trial of pertuzumab retreatment in HER2-positive locally advanced/metastatic breast cancer patients previously treated with pertuzumab, trastuzumab and chemotherapy: the Japan Breast Cancer Research Group-M05 PRECIOUS study. (18th July 2018) - Yamamoto, Yutaka; Iwata, Hiroji; Ueno, Takayuki; Taira, Naruto; Kashiwaba, Masahiro; Takahashi, Masato; Tada, Hiroshi; Tsugawa, Koichiro; Toyama, Tatsuya; Niikura, Naoki; Hara, Fumikata; Fujisawa, Tomomi; et al.
Abstract : The PRECIOUS, a multicenter, randomized, open-label Phase III study, is to determine whether pertuzumab retreatment is more effective than conventional treatment in HER2-positive advanced breast cancer patients previously receiving pertuzumab. Abstract: The PRECIOUS study (UMIN000018202) is being conducted as a multicenter, randomized, open-label Phase III study to determine if retreatment with pertuzumab is more effective than conventional treatment in HER2-positive locally advanced (LA)/metastatic breast cancer (MBC) patients previously treated with pertuzumab, trastuzumab and chemotherapy. Patients are randomized 1:1 into chemotherapy plus trastuzumab with or without pertuzumab groups. The latest regimen before enrollment did not include pertuzumab, and the number of previous chemotherapy regimens for LA/MBC did not exceed three. The primary endpoint is investigator-assessed progression-free survival. Secondary endpoints include independent reviewer-assessed progression-free survival, progression-free survival in patients treated with trastuzumab emtansine as the latest regimen, response rate, response duration, overall survival, safety and health-related quality of life. Target accrual is 370 patients, allowing the observation of 325 events, yielding an 80% power for detection of a hazard ratio of 0.739 with a one-sided 5% level of significance.